EFL Students’ Metacognitive Knowledge on Speaking Strategies - Abdul Chasib; Anwar, Khoirul; Asmara, Candra Hadi (Journal of English Teaching, Literature, and Applied Linguistics, 2026)
This study investigated EFL students’ metacognitive knowledge in speaking, focusing on the types of strategies most frequently used and the areas requiring improvement. Using a descriptive quantitative design, data were collected from 102 English Education students at Muhammadiyah University of Gresik through the Metacognitive Awareness Speaking Questionnaire (MASQ). The findings showed that students most frequently used Strategic Knowledge, particularly problem-solving and planning and evaluation strategies, indicating a strong ability to manage and regulate their speaking performance. In contrast, lower levels were found in Person Knowledge and Mental Translation, suggesting limited self-awareness of speaking abilities and continued reliance on first-language translation. These results indicate that while students are generally effective in controlling and adapting their speaking strategies, greater emphasis is needed on developing self-awareness and reducing translation dependency to support more autonomous and fluent English speaking.